Successful management of severe anaerobic infection inducing mediastinal and subcutaneous emphysema, septic shock, and ARDS: a case report highlighting VV-ECMO and NGS-guided therapy - Wu, Haohao; Lan, Pin; Zhou, Kechun; Wu, Xingzhen; Xie, Lutao (Frontiers in Medicine, 2025)
BackgroundMediastinal and cervical subcutaneous emphysema caused by anaerobic infections is rare in clinical practice, particularly when accompanied by sepsis, septic shock, and severe acute respiratory distress syndrome (ARDS). These cases pose significant treatment challenges. Veno-venous extracorporeal membrane oxygenation (VV-ECMO), as a life-saving intervention, has been increasingly utilized in patients with severe infections and refractory hypoxemia. This report aims to evaluate the effectiveness of VV-ECMO in the treatment of mediastinal and subcutaneous emphysema, sepsis, and severe ARDS caused by anaerobic infections, and to summarize relevant therapeutic strategies.Case presentationA 49-year-old male was admitted with fever, sore throat, chest tightness, and hoarseness. On admission, he presented with severe hypoxemia, sepsis, and acute kidney injury. Chest computed tomography (CT) revealed bilateral mediastinal emphysema and cervical subcutaneous emphysema. Next-generation sequencing (NGS) confirmed an anaerobic bacterial infection. Despite high-flow oxygen therapy and antibiotic treatment, the patient’s oxygenation continued to deteriorate, culminating in cardiopulmonary arrest. VV-ECMO was initiated to improve oxygenation, alongside prone positioning ventilation, sputum clearance, and alveolar lavage. After 7 days of ECMO support and anti-infective treatment, the patient’s oxygenation improved significantly, inflammatory markers decreased, and ECMO was successfully weaned.ConclusionVV-ECMO is of critical value in managing septic shock and ARDS caused by severe anaerobic infections, effectively improving oxygenation and supporting organ function. This case highlights the pivotal role of airway management, VV-ECMO support, and comprehensive therapeutic strategies in the management of complex infectious ARDS, providing valuable insights for similar clinical scenarios.